2020
DOI: 10.1093/ofid/ofaa100
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Urine-Based Tuberculosis (TB) Screening With TB-Lipoarabinomannan and Xpert MTB/RIF Ultra in Ugandan Adults With Advanced Human Immunodeficiency Virus Disease and Suspected Meningitis

Abstract: Background Diagnosis of extrapulmonary tuberculosis (TB) remains challenging. We sought to determine the prevalence of disseminated TB by testing urine with TB-lipoarabinomannan (TB-LAM) lateral flow assay and Xpert MTB/RIF Ultra (Ultra) in hospitalized adults. Methods We prospectively enrolled human immunodeficiency virus (HIV)-positive adults with suspected meningitis in Uganda during 2018–2020. Participants underwent stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Concordance of Xpert MTB/RIF and LF-LAM in this cohort was low, but in line with other studies (Cresswell et al, 2020). In a previous study in Mozambique, a higher concordance was found between the two tests (Floridia et al, 2017); however, these variations could be attributed to different rates of extrapulmonary TB, due to different patient selection criteria.…”
Section: Discussionsupporting
confidence: 89%
“…Concordance of Xpert MTB/RIF and LF-LAM in this cohort was low, but in line with other studies (Cresswell et al, 2020). In a previous study in Mozambique, a higher concordance was found between the two tests (Floridia et al, 2017); however, these variations could be attributed to different rates of extrapulmonary TB, due to different patient selection criteria.…”
Section: Discussionsupporting
confidence: 89%
“…A novel LAM assay has increased sensitivity and thus might allow prevention of unmasking IRIS [123]. Tests of both urine and sputum with GeneXpert MTB/RIF Ultra can also improve detection of TB in PLHIV, and return results quickly enough to allow for providing ATT at the time of ART-initiation [173][174][175], potentially allowing prevention of unmasking IRIS [158].…”
Section: Risk Factors and Preventionmentioning
confidence: 99%
“…The study included Ugandan adults presenting with first-episode cryptococcal meningitis After conclusion of ASTRO-CM, participants were enrolled in an observational cohort focused on meningitis diagnostics. [12][13][14] All participants enrolled into the studies provided written informed consent. Participants were treated with standard antifungal therapy and those who were enrolled into ASTRO-CM were randomized to either receive adjunctive sertraline (400 mg/day for 14 days, followed by 200 mg/day for 12 weeks) or placebo.…”
Section: Study Design and Participantsmentioning
confidence: 99%